The Application of Deep-Breathing Relaxation Techniques with Lemon Aromatherapy to Reduce Pain in Post–Sectio Caesarea Mothers at RSUD dr. Adhyatma, MPH, Central Java Province - Febta Fatmia Ardani; Witri Hastuti (Jurnal EduHealth, 2025)
Post–sectio caesarea mothers often experience significant postoperative pain that interferes with mobility, breastfeeding initiation, and overall recovery. Pharmacological pain management such as analgesics provides rapid relief but may cause side effects when used long term. Therefore, non-pharmacological interventions are needed to complement pharmacological approaches safely. This study aimed to determine the effectiveness of deep-breathing relaxation techniques combined with lemon aromatherapy in reducing postoperative pain among post–sectio caesarea mothers at RSUD dr. Adhyatma, MPH, Central Java Province. This descriptive case study involved two respondents selected through purposive sampling based on inclusion and exclusion criteria. Data were collected using observation sheets, nursing documentation, interviews, and direct observation, while pain intensity was measured using the Numerical Rating Scale (NRS) before and after the intervention. The results showed a significant decrease in pain intensity after two consecutive days of intervention. In Patient 1, the pain scale decreased from 5 to 4 on the first day and from 4 to 2 on the second day, while in Patient 2, it decreased from 6 to 5 and from 4 to 3, respectively. Both patients reported improved comfort, relaxation, and self-control in managing postoperative pain. These findings indicate that deep-breathing relaxation combined with lemon aromatherapy is an effective, simple, and safe non-pharmacological nursing intervention to complement pharmacological pain management and enhance postoperative recovery among post–sectio caesarea patients.